Rapid detection of Pseudomonas aeruginosa targeting the toxA gene in intensive care unit patients from Beijing, China - Dong, Derong; Zou, Dayang; Liu, Hui; Yang, Zhan; Huang, Simo; Liu, Ningwei; He, Xiaoming; Liu, Wei; Huang, Liuyu (Frontiers in Microbiology, 2015)
Pseudomonas aeruginosa is a major opportunistic pathogen in hospital-acquired infections and exhibits increasing antibiotic resistance. A rapid and sensitive molecular method for its detection in clinical samples is needed to guide therapeutic treatment and to control P. aeruginosa outbreaks. In this study, we established a polymerase spiral reaction (PSR) method for rapid detection of P. aeruginosa by targeting the toxA gene, which regulates exotoxin A synthesis. Real-time turbidity monitoring and a chromogenic visualization using hydroxynaphthol blue were used to assess the reaction. All 17 non- P. aeruginosa strains tested negative, indicating the high specificity of the PSR primers. The detection limit was 2.3 pg/µl within 60 min at isothermal temperature (65°C), 10-fold more sensitive than conventional PCR. Then, the PSR assay was applied to a clinical surveillance of P. aeruginosa in three top hospitals in Beijing, China. Of the 130 sputum samples collected from ICU patients with suspected multi-resistant infections, 37 P. aeruginosa isolates were identified from the positive samples. All clinical strains belonged to 10 different P. aeruginosa multilocus sequence typing groups and exhibited high resistance to carbapenems, cephalosporins, and aminoglycosides. Interestingly, of the 33 imipenem-resistant isolates, 30 (90.9%) had lost the outer membrane porin oprD gene. Moreover, isolate SY-95, containing multiple antibiotic resistance genes, possessed the ability to hydrolyze all antibiotics used in clinic and was susceptible only to polymyxin B. Our study showed the high level of antibiotic resistance and co-occurrence of resistance genes in the clinical strains, indicating a rapid and continuing evolution of P. aeruginosa. In conclusion, we developed a P. aeruginosa PSR assay, which could be a useful tool for clinical screening, especially in case of poor resources, or for point-of-care testing.